2006
DOI: 10.1177/0895904805285017
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Connection Between Higher Education Policy and Performance

Abstract: In 1997, the state of South Dakota instituted an incentive program to reward institutions for performance related to state policy priorities. The program had a specified starting and ending point, running its course in 2002. This program provides a unique opportunity to study the connection between higher education policy and performance, an issue of central concern in most states as they try to maximize their use of existing state resources. The analysis uses literature and concepts from existing higher educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…They, however, were unsure of whether the reform contributed to institutional efficiency. Martinez and Nilson (2006) evaluated a new accountability initiative in South Dakota and found that the new accountability contributed to improving institutional performance measured against five academic goals-resident student enrollment, student enrollment in economic growth programs, academic improvement, collaboration, and attracting external funding.…”
Section: Impacts Of New Accountabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…They, however, were unsure of whether the reform contributed to institutional efficiency. Martinez and Nilson (2006) evaluated a new accountability initiative in South Dakota and found that the new accountability contributed to improving institutional performance measured against five academic goals-resident student enrollment, student enrollment in economic growth programs, academic improvement, collaboration, and attracting external funding.…”
Section: Impacts Of New Accountabilitymentioning
confidence: 99%
“…Some studies address this question. Martinez and Nilson (2006) looked at South Dakota's performance funding and found that state accountability contributed to institutional performance to some extent. Volkwein and Tandberg (2008), however, determined that state accountability did not contribute to state grades in Measuring Up 2002, 2004.…”
Section: Introductionmentioning
confidence: 98%
“…As it related to the persistence to graduation rate for freshmen cohorts in universities, the rate increased from 43.1% in 1985 to 50.4% in 2002; in community colleges, the rate increased from 25.0% in 1985 to 31.0% in 2002. South Dakota also developed an incentive program in 1997 to reward state universities for performance related to nine state policy goals, including access to higher education, incentives for persistence to graduation, and efficiency (Martinez & Nilson, 2006). The program is a case study for how states attempt to get the most of their resources through educational policy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are several critical indexes of performance evaluation, such as administration, teaching, research, students' learning outcomes, society responsibility, and financial sustainability, to help decision makers to allocate resources in annual accountability reports. Through surveys and analyses, institutions share their performance with the public and link institutional performance with budget allocation [3][4][5]. According to some certified world university rankings, such as the Quacquarelli Symonds (QS) World University Rankings, the Times Higher Education (THE) World University Rankings, the Academic Ranking of World Universities (ARWU), and the Webometrics Ranking of World Universities, institutional performance can be evaluated effectively.…”
Section: Introductionmentioning
confidence: 99%